Implication Of Malaysia’s Movement Control Order Towards Online News Reading Preference Among Public University Students - Saiful Nujaimi Abdul Rahman; Amir Ali Rosli; Norliana Hashim; Sharifah Sofiah Syed Zainudin (Ikatan Sarjana Komunikasi Indonesia, 2022)
Online news publication had undergone revolutionary changes since the fall of Berlin Wall, 09 November 1989. When Malaysian Government regulated the Movement Control Order (MCO) beginning 18 March 2020 till 03 January 2022 to curb the spread of COVID-19 pandemic, the impact of online news reading became much more significant. This phenomena has brought massive implications to media audience, predominantly among university students – of which, utilizing most of the online news material for their academic references. The online news became major reading materials for the university students in deriving latest information, especially on COVID-19 pandemic. Thus, this study was conducted to identify its implications, news preferences, and satisfaction levels. This purposive random quantitative study had been conducted by disseminating questionnaires via online, due to the restriction of movements. A total of 400 respondents were involved in this study, and interesting findings had been discovered. The study was purposively focused on random public university students within The Klang Valley, due to the fact that students from these universities had been the nation’s catalyst of change ever since. Conclusively, this paper provides significant insights for media practitioners and consumers in developing pertinent strategies for better maneuvering such challenges in our digital future.